THE SHARING ECONOMY AND COLLABORATIVE FINANCE: THE CASE OF P2P LENDING IN VIETNAM - Tran Dinh Uyen; Hoang Ha (Jurnal Ilmiah Ekonomi Bisnis, 2017)
Peer-to-peer Online Lending (P2PO) has received increasing attention over the last years, not only because of its disruptive nature and its disintermediation of nearly all major banking functions, but also because of its rapid growth and expanding breadth of services. This model offers a new way of investing in addition to investing in traditional channels such as banking or financial company. The transaction process is done online, the personal information and terms of mobilization are completely transparent and secure in the best way. The strong development of P2PO also raises a number of issues that require careful attention to promote positive and to limit negative aspects. The research aims to highlight particular aspects of this new business model and to analyze the opportunities and risks for lenders and borrowers in Viet Nam. The research combines qualitative analysis and data survey to serve descriptive statistics about P2PO in Viet Nam. The research show the potential of online peer lending is enormous but the regulators will restrict the Sharing economy model in general and P2PO lending in particular Keywords: Sharing economy, P2P lending, financial innovation, Disintermediation, Fintech